The Effect of Adding Rabbit Urine POC on the Production of Three Pak choi Plants by Hydroponic Wick System - Ahmad Aliwinarjo; Nur Iman Muztahidin; Abdul Hasyim Sodiq; Yayu Romdhonah (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2022)
The hydroponic system is still constrained by the high cost of AB mix nutrients. This study aimed to determine the effect of adding rabbit urine as Liquid Organic Fertilizer (LOF) to the nutrient solution on the growth and yield of three varieties of pak choi (Brassica rapa L.) with a wick hydroponic system. The experiment used a split plot design for the main plot of LOF (K) which consisted of 3 levels, namely control (K0), mixture AB + 6 ml/l LOF (K1), and mixed AB + 12 ml/l LOF (K2), and sub plot of varieties (V) consisting of 3 levels, namely Nauli f1 (V1), Emone 26 (V2) and Green (V3). The results showed that increasing the concentration of LOF in rabbit urine in 12 ml/l nutrient solution did not have any significantly different result on the growth and yield of pak choi plants. However, Emone 26 varieties showed a very significant effect on growth and yield, with average values on the parameters of plant height, number of leaves, fresh weight, crown fresh weight and crown dry weight at 35 Days After Planting (DAP). 25.14 cm, 14.22 pieces, 94.69 g, 79.06 g, and 4.43 g, respectively. There was no interaction between the addition of LOF rabbit urine to the growth and yield of three varieties of pak choi on all parameters observed. Further research needs to be done on other hydroponic systems in order to obtain the right POC concentration to reduce the use of AB mix nutrients.